2009
DOI: 10.1128/aem.02032-08
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an Allele Conferring Resistance to Bacillus sphaericus Binary Toxin in Culex quinquefasciatus Populations by Molecular Screening

Abstract: The activity of the Bacillus sphaericus binary (Bin) toxin on Culex quinquefasciatus larvae depends on its specific binding to the Cqm1 receptor, a midgut membrane-bound ␣-glucosidase. A 19-nucleotide deletion in the cqm1 gene (cqm1 REC ) mediates high-level resistance to Bin toxin. Here, resistance in nontreated and B. sphaericus-treated field populations of C. quinquefasciatus was assessed through bioassays as well as a specific PCR assay designed to detect the cqm1 REC allele in individual larvae. Resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 44 publications
2
35
1
Order By: Relevance
“…Susceptibility to B. sphaericus in two nontreated populations of IPO and JAB showed that RR values at the LC 90 were similar to that of the reference colony, and the slight variations in RRs found at the LC 50 are comparable to previous RRs reported for other nontreated mosquito populations, which have demonstrated the existence of natural variations in their B. sphaericus susceptibilities (4,20,34,36,37). The status of two other nontreated populations of ROD and AZE could not be analyzed; nevertheless, they were expected to be susceptible since B. sphaericus had not been used in these areas and they were also geographically isolated from the only two exposed areas in RMA at the time the samples were collected (28,31).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Susceptibility to B. sphaericus in two nontreated populations of IPO and JAB showed that RR values at the LC 90 were similar to that of the reference colony, and the slight variations in RRs found at the LC 50 are comparable to previous RRs reported for other nontreated mosquito populations, which have demonstrated the existence of natural variations in their B. sphaericus susceptibilities (4,20,34,36,37). The status of two other nontreated populations of ROD and AZE could not be analyzed; nevertheless, they were expected to be susceptible since B. sphaericus had not been used in these areas and they were also geographically isolated from the only two exposed areas in RMA at the time the samples were collected (28,31).…”
Section: Discussionsupporting
confidence: 73%
“…The treated population of AGU evaluated here showed a higher cqm1 REC frequency than those from the nontreated populations, which is consistent with B. sphaericus exposure in that area. However, this frequency has not increased compared to previous screenings performed in AGU (4,32), suggesting that the selection pressure might be low. This could be related with the introduction of Bacillus thuringiensis serovar israelensis (B. thurin- The premature translation stop codon originating from the deletions described here is boxed in bold.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Cases of resistance to these alternative insecticides are still limited (Rivero et al, 2010) and the underlying mechanisms are only beginning to be identified (Chalegre et al, 2009;Darboux et al, 2007 Adapted from Rivero et al (2010). Metabolic resistance: EST, enhanced esterase activity; GST, enhanced glutatione-S-transferase activity; MOX, enhanced p450 monoxygenase activity.…”
Section: Insecticide Resistance Mechanismsmentioning
confidence: 99%